1992
DOI: 10.1111/j.1440-1746.1992.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CA19‐9 production in vitro and histological grades of differentiation in vivo in clones isolated from a human pancreatic cancer cell line (SUIT‐2)

Abstract: The production of carcino-embryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) were investigated in 28 clones isolated from a human pancreatic cancer cell line (SUIT-2) and related to in vitro morphology of the clones and in vivo tumorigenicity. Clones of fusiform and polygonal cells could be morphologically distinguished in confluent cultures. There was no significant difference in CEA production between fusiform-cell clones (2.10 +/- 2.70 ng/L x 10(6) per 24 h) and polygonal-cell clones (6.01 +/- 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Panc1 is a poorly differentiated human pancreatic adenocarcinoma cell line that expresses low levels of endogenous MUC1 and relatively low levels of other glycoproteins (28). S2-013 is a moderately differentiated human pancreatic tumor cell line that is known to express abundant O-glycosylated mucin-like proteins, including low levels of endogenous MUC1 (23). cDNA constructs encoding FLAG epitope-tagged forms of MUC1 have been described previously (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panc1 is a poorly differentiated human pancreatic adenocarcinoma cell line that expresses low levels of endogenous MUC1 and relatively low levels of other glycoproteins (28). S2-013 is a moderately differentiated human pancreatic tumor cell line that is known to express abundant O-glycosylated mucin-like proteins, including low levels of endogenous MUC1 (23). cDNA constructs encoding FLAG epitope-tagged forms of MUC1 have been described previously (12).…”
Section: Resultsmentioning
confidence: 99%
“…Panc1 was obtained from the American Type Culture Collection. S2-013 is a cloned subline of a human pancreatic tumor cell line (SUIT-2) derived from a liver metastasis (23). Armenian Hamster monoclonal antibody (mAb) CT2 against the MUC1CT was kindly provided by Dr. Sandra J. Gendler (Mayo Clinic, Scottsdale, AZ).…”
Section: Methodsmentioning
confidence: 99%
“…The STR profile also showed that they were novel cell lines and free from cell line cross-contamination. The expression of cytokeratin, CA19-9 and CEA (33)(34)(35), and tumorigenicity in mice indicated that they were pancreatic cancer cells. Moreover, the corresponding cell line xenograft tumors preserved similar pathological profiles and differentiation compared with their clinical samples and human primary tumors, which suggested that these low passage tumor cells maintained the clinical characteristics of pancreatic carcinoma, which could represent pancreatic tumor models both in vitro and in vivo, and help in translation of clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…The first, Panc-1, is a poorly differentiated human pancreatic adenocarcinoma cell line that expresses low levels of endogenous MUC1 and relatively low levels of other glycoproteins (37). The second, S2-013, is a moderately differentiated human pancreatic tumor cell line that is known to express O-glycosylated mucin-like proteins, including low levels of endogenous MUC1 (38).…”
Section: Transfection Of Cell Lines and Expression Of Muc1 Deletionmentioning
confidence: 99%